Determinants of ecological footprint in MINT countries - Dogan, Eyup; Taspinar, Nigar; Gokmenoglu, Korhan K. (Sage Publications Ltd, 2019)
Environmental Kuznets curve literature mostly uses a single indicator as a measure for environmental degradation. However, each single variable captures only a part of the environmental problem, and a reduction in any single measure does not indicate that the environmental problem is diminishing in general. Our study is the first one which investigates the validity of the environmental Kuznets curve hypothesis for the Mexico, Indonesia, Nigeria, and Turkey (MINT) countries by employing the ecological footprint as the measure of environmental degradation. Autoregressive distributed lag results indicate that the environmental Kuznets curve hypothesis is valid for each of the MINT countries for the period of 1971-2013. The long-run coefficients of our augmented environmental Kuznets curve model show that fossil fuel energy consumption, exports, urbanization, and financial development are the most common causes of anthropogenic pressure on the environment. The effects of exports and imports are negative and positive on environmental degradation, respectively. The long-run coefficients of urbanization, financial development, and renewable energy consumption differ at certain levels for the sampled countries. The results of the analysis point to a number of different policy proposals for each country.
Keywords: Environmental degradation; environmental Kuznets curve; trade; renewable energy